2. Characterization of the tuberous sclerosis complex population in the province of Quebec: Healthcare services utilization and long term outcome. Issue 4 (April 2016) - Bernier, A.; Landry, J.S.; Kristof, A.S.; Carmant, L.; Major, P.
Abstract : Background: Tuberous sclerosis complex (TSC) is a neurocutaneous syndrome that can present with many disabling neurological disorders, the most common being epilepsy. Although it is a chronic multi-system disease, healthcare utilization and long-term outcome of subjects with TSC are not yet well defined. The goal of this study was to evaluate the direct cost and long-term outcome of TSC in the province of Quebec, compared to other forms of epilepsy and healthy controls. Methods: Our provincial health care database was interrogated to determine use of medical services by patients with TSC, epilepsy and healthy controls from 1996 to 2011. Data on demographics, outcomes and health care utilization were analyzed. Results: 1004 TSC, 41, 934 with epilepsy and 41, 934 controls were identified. The prevalence of TSC was 1/7872 compared to 1/189 for epilepsy. TSC experienced more hospitalizations, medical visits and prescription drug use. Their most common admission diagnosis was seizures and age at death was significantly lower: 61.3 years old for TSC vs 69.6 and 76.6 years old for epilepsy and controls ( p < 0.001 ). Conclusions: TSC subjects have a significantly higher burden of disease than other subjects with epilepsy. These results stress the need for specialized services in this population through the lifespan.